(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objectives: To analyze the relationships between the quality of life (QOL) of people with stoma with sociodemographic, clinical, lifestyle, sanitation, and housing indicators. Method: Cross-sectional study with a sample of 106 individuals with stoma interviewed from May to December 2019. A sociodemographic and clinical questionnaire and the City of Hope Quality of Life Ostomy Questionnaire were used. Results: Spiritual well-being (7.71 +/-1.09) was the best performing domain. Quality of life did not differ between men and women (p = 0.372), but was associated with education (< 0.001) and family income (p = 0.025), diabetes (p = 0.008) and alcoholism (p = 0.044), drinking water conditions (p < 0.001), garbage disposal (p = 0.021), having electricity (p = 0.034), housing type (p = 0.026), number of rooms (p = 0.023), and housing coverage (p = 0.021). Conclusion: worse socioeconomic, sanitation, and housing indicators appear to negatively impact the QOL of people with stomata.